Social Reality in Discourse of «Objectification Turn» - I. V. Katerny (Vestnik MGIMO-Universiteta)
Since the late 7 970s - early 1980s a large body of research has been under way to discern social manifestations of physical space and to perceive the social role of objects within - from familiar utility devices to frightening nature disasters. Recent decades of social change feature the transformation of initially non-social substance (material objects, virtual images, cyber-messages, as well as natural disasters) into active modulators of social processes. This results in the "postsocial relations", that is social enaction of various kinds of objects, which leads to the fact that non-human, non-living and even non-physical objects are increasingly replacing humans as partners to communicate with and deeply mediating social relations, making the latter dependent on them. Thus, the explosion-like expansion of object-centered milieu in the human world consistently fuels the intellectual interest in the analysis of поп-subjective dimension of the social. This trend in the social sciences and humanities may be defined as objectological turn. The proposed paper summarizes some developments in the social objectoiogy, a new research domain related to studying the practice of mixed (hybrid) communication of people with various material and non-material objects. The author highlights the relevant approaches and their contributors, and provides analysis of the "objectological thought" in the history of social theory. Also, in the paper there is the classification of social objects based on their spatial scale, forming object-centered environment from the micro to the macro level.